L'on y joue, l'on y danse: quatro datas e um novo director sur le Pont d'Avignon - Silva, Alexandra Moreira da (Sinais de Cena, 2014)
L'on y joue, l'on y danse: quatro datas e um novo director sur le Pont d'Avignon